Students’ Worksheets Based on Problem Based Learning In Composition and Inverse Functions to Enhance Conceptual Understanding - Mia Priyanto; Dian Permatasari (Department of Mathematics Education, Faculty of Tarbiyah and Teacher Training, UIN Sunan Ampel Surabaya, 2022)
This research aims to design student worksheets based on problem-based learning in composition and inverse functions to facilitate conceptual understanding is valid. This research uses a PPE model by Richey and Klein; there are three parts: planning, production, and evaluation. The planning stage is a product planning process that will be developed for a specific purpose. The production stage is the process of making a product according to a previously made design. The evaluation stage is the process of testing and assessing the product that has been developed. The data obtained from the expert validator is then processed using a Likert scale and calculated using Aiken's formula to conclude the validity of the product developed. The Student Worksheets based on Problem Based Learning to aid students' understanding of mathematical ideas on composition functions and inverse functions were valid, have a 0.84 average validity value, and were classified as high. The PBL model familiarizes students with understanding concepts through problem-solving processes. On the other hand, learning mathematics using PBL effectively improves students' understanding and abilities because students apply mathematical concepts in everyday life.